The Contribution of Phosphocreatine during the Wingate Anaerobic Test in Men and Women. - Saghiv, M; Sagiv, M (British Journal of Healthcare and Medical Research, 2023)
Purpose: the purpose of this study was to compare the relative contribution of phosphocreatine to the overall energy supply during the Wingate Anaerobic Test in men and women. Methods: Forty well trained cyclist, 20 men (23.0±1.1 years) and 20 women (23.4±1.1 years) performed the Wingate Anaerobic Test to estimate the relative contribution of the phosphocreatine. Results: In both groups, first 5 second power output peaked significantly (p<0.05), differences were noted between men and women in: pedaling revolutions for first 10 seconds (28.0±0.7 and 23.4±1.0 respectively), revolutions per 30 seconds (64.5±1.7 and 55.9±1.9 respectively), Lactate levels at 10th,15th and 30th seconds (3.2±0.3, 5.4±0.4 and 12.2±0.7 Vs. 2.8±0.3, 4.8±0.4 and 10.4±0.5 mmol∙L-1 respectively). Conclusions: Gender differences in the absolute muscle mass involved in the activity and workload performed during the Wingate Anaerobic Test might explain the significant differences in absolute power output and fatigue rate. During the Wingate Anaerobic Test phosphocreatine is the predominant energy system in men and women contributing 40% of the total energy expenditure. However, since there is less amount of stored CP and ATP in women’s skeletal muscles involved, fatigue occurs earlier than in men. Metabolism and adaptive response to cycling training, may reduce gender-related differences in performance.